Mechanical determinants of sprint performance in elite and sub-elite field hockey players - Vanwanseele, B.; Aeles, J. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of the present study was to investigate the difference in the horizontal mechanical determinants of sprint performance in highly-trained elite field hockey players versus sub-elite field hockey players. Thirty-five highly trained field hockey players (1 8 elite international players and 17 sub-elite players) were tested during the competitive season. They performed a maximal 40 meter sprint. Distance was tracked over time via a 312 Hz laser (Laser Technology, Inc) and used to calculate, for each individual, a horizontal force-velocity profile. Elite players showed a larger theoretical maximal horizontal velocity (vO) compared to the sub-elite hockey players. No significant differences in theoretical maximal horizontal force (FO) and horizontal power (Pmax) between the groups were observed. Large variability especially in the sub-elite groups was observed in FO and vO, indicating the potential for individualized training program focusing on the weaker parameter.